2013
DOI: 10.1002/cne.23334
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the midbrain periaqueductal gray modulates preinspiratory neurons in the ventrolateral medulla in the rat in vivo

Abstract: The midbrain periaqueductal gray (PAG) is involved in many basic survival behaviors that affect respiration. We hypothesized that the PAG promotes these behaviors by changing the firing of preinspiratory (pre-I) neurons in the pre-Bötzinger complex, a cell group thought to be important in generating respiratory rhythm. We tested this hypothesis by recording single unit activity of pre-Bötzinger pre-I neurons during stimulation in different parts of the PAG. Stimulation in the dorsal PAG increased the firing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 59 publications
1
44
1
Order By: Relevance
“…In contrast, in intact animals, stimulation of the dorsolateral PAG column does trigger both the somatomotor, cardiovascular and respiratory changes characteristic of active coping (Bandler et al, 1985;Depaulis and Vergnes, 1986;Yardley and Hilton, 1987;Bandler and Depaulis, 1988;Morgan and Franklin, 1988;Depaulis et al, 1989Depaulis et al, , 1992Zhang et al, 1990;Morgan et al, 1998;Horiuchi et al, 2009;Dampney et al, 2013;Subramanian and Holstege, 2013). These observations strongly suggest that the cardio-respiratory component of active coping integrated by the dlPAG, depends critically on a relay rostral to the mesencephalon.…”
Section: Brainstem Efferentscontrasting
confidence: 48%
See 1 more Smart Citation
“…In contrast, in intact animals, stimulation of the dorsolateral PAG column does trigger both the somatomotor, cardiovascular and respiratory changes characteristic of active coping (Bandler et al, 1985;Depaulis and Vergnes, 1986;Yardley and Hilton, 1987;Bandler and Depaulis, 1988;Morgan and Franklin, 1988;Depaulis et al, 1989Depaulis et al, , 1992Zhang et al, 1990;Morgan et al, 1998;Horiuchi et al, 2009;Dampney et al, 2013;Subramanian and Holstege, 2013). These observations strongly suggest that the cardio-respiratory component of active coping integrated by the dlPAG, depends critically on a relay rostral to the mesencephalon.…”
Section: Brainstem Efferentscontrasting
confidence: 48%
“…Active emotional coping reactions have also been reported following electrical or chemical stimulation of the dmPAG/deep layers of the superior colliculus (see, for example, Krieger and Graeff, 1985). bradycardia and tachypnea, (Subramanian and Holstege, 2013). The behavioral significance of such changes has been studied less frequently, although evidence points to an important role for the dmPAG in conditioned fear responses to social threat/s (Faturi et al, 2013).…”
Section: Brainstem Efferentsmentioning
confidence: 98%
“…In particular, lactate-induced panic attacks are characterised by early dyspnoea, followed by panic, desire for flight and a sustained hyperventilation that continues several minutes after the end of the infusion. Subramanian and Holstege (2013) showed that the firing of pre-inspiratory neurons of the pre-Bötzinger complex (i.e., the cells thought to generate the respiratory rhythm) was affected differently by chemical stimulations of distinct parts of the LPAG. Therefore, stimulations in the medial aspect of the LPAG produced inspiratory apneusis and transformed pre-inspiratory neurons into phase-spanning neurons that discharge at transition from inspiration to expiration.…”
Section: Role Of the Periaqueductal Grey Matter In Respirationmentioning
confidence: 99%
“…From the behavioral perspective, the preBötC is not the only region that participates in breathing. Additional areas can be found in the medulla, the pons, the cerebellum, the cortex, the amygdala, the hypothalamus, and the periaqueductal gray (PAG) (Brannan et al, 2001; Burdakov et al, 2013; Chamberlin and Saper, 1994; Liotti et al, 2001; Masaoka et al, 2012; Nattie and Li, 2012; Ramirez et al, 2012; Smith et al, 2009; Subramanian and Holstege, 2013). The contribution of each of these areas adds different and important aspects to the neuronal control of breathing making breathing one of the most modulated and complex behaviors.…”
Section: The Concept Of Network Reconfigurationmentioning
confidence: 99%